2001
DOI: 10.1001/archinte.161.22.2725
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Pneumonia in an Employed Population

Abstract: Patients with pneumonia present an important financial burden to employers. These patients use more medical care services, particularly inpatient services, than the average beneficiary in the employer overall population. In addition to direct health care costs related to medical utilization and the use of prescription drugs, indirect costs due to disability and absenteeism also contribute to the high cost of pneumonia to an employer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 10 publications
1
26
0
1
Order By: Relevance
“…NIEDERMAN et al [5] and WITTLE et al [13] in the USA have reported that 95 and 81%, respectively, of the overall costs of treating pneumonia were associated with inpatient care. In the study of BIRNBAUM et al [34], carried out in employed persons, this percentage decreased to 63.…”
Section: Discussionmentioning
confidence: 89%
“…NIEDERMAN et al [5] and WITTLE et al [13] in the USA have reported that 95 and 81%, respectively, of the overall costs of treating pneumonia were associated with inpatient care. In the study of BIRNBAUM et al [34], carried out in employed persons, this percentage decreased to 63.…”
Section: Discussionmentioning
confidence: 89%
“…Although a number of studies have reviewed the care burden of either COPD or pneumonia, no studies have quantified the burden of pneumonia in patients with COPD 1114. Costs for patient care associated with COPD are assumed to increase with the development of pneumonia, though few studies have directly investigated this question in a real-world setting 15.…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which our results may be generalisable to other different epidemiological settings where incidence of community acquired pneumonia may be higher [4][5][6] remains to be determined.…”
Section: Discussionmentioning
confidence: 92%